Passing Exercise Model In Game Soccer For SMP Students - Arinda Wahyu Safitri; Fransiskus Nurseto; Rahmat Hermawan (JUPE (Jurnal Penjaskesrek), 2019)
The problem in this study was the still low level of passing skills of the football extracurricular students at Tri Sukses Natar Middle School in South Lampung. The aim to be achieved in this research and development is to produce a model of soccer passing training. This study uses the Research Development (R D) method. The subjects in this study were junior high school students who took football extracurricular activities. Product effectiveness test is based on the assessment of football experts, learning experts, and linguists. The value obtained is 84.41% which is stated to be quite valid and feasible to use. Based on the results of the development it can be concluded: (1) The training model developed can be applied in the training process (2) This model of soccer passing training can improve students' passing skills, (3) As a contribution to education science especially in the field of football especially for middle school students.Masalah dalam penelitian ini adalah masih rendahnya tingkat keterampilan passing siswa ekstrakurikuler sepakbola SMP Tri Sukses Natar Lampung Selatan. Tujuan yang ingin dicapai pada penelitian dan pengembangan ini adalah untuk menghasilkan produk model latihan passing sepakbola. Penelitian ini menggunakan metode Research Development (RD). Subyek dalam penelitian ini adalah siswa SMP yang mengikuti ekstrakulikuler sepakbola.Uji efektifitas produk yaitu berdasarkan penilaian ahli sepakbola, pembelajaran, dan ahli bahasa. Nilai yang di dapatkan adalah 84,41% yang dinyatakan cukup valid dan layak untuk digunakan. Berdasarkan hasil pengembangan dapat disimpulkan : (1) Model latihan yang dikembangkan dapat diterapkan dalam proses latihan (2) Model latihan passing sepakbola ini dapat meningkatkan kemampuan passing siswa, (3) Sebagai sumbangan bagi ilmu pendidikan khususnya bidang sepakbola khususnya bagi siswa SMP.keywords : Passing, Model, Training, Football,